Borges, el Quijote y los cervantistas españoles - Pastormerlo, Sergio Carlos (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2006)
Quixote has an almost excessive presence in the work of Jorge Luis Borges. The intense relationship of Borges with Cervantes' novel, nevertheless, is lavish in equivocal appraisals and misunderstandings. The article explores and comments on some of these misunderstandings, reconstructing its contexts in the framework of Borges' vast production as a critic. His concept of 'superstition', his ill-timed anti-Hispanism, his bonds with Quevedo, and the tendency of his criticism to dialogue or discuss with other critical discourses are the main axes of this proposed reading.